2017
DOI: 10.1002/14651858.cd011432.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase tuberculosis case detection at primary healthcare or community-level services

Abstract: BackgroundPulmonary tuberculosis is usually diagnosed when symptomatic individuals seek care at healthcare facilities, and healthcare workers have a minimal role in promoting the health-seeking behaviour. However, some policy specialists believe the healthcare system could be more active in tuberculosis diagnosis to increase tuberculosis case detection.ObjectivesTo evaluate the effectiveness of different strategies to increase tuberculosis case detection through improving access (geographical, financial, educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 75 publications
6
63
0
2
Order By: Relevance
“…Systematic reviews have reported ACF to be beneficial in increasing case detection [5,6]. Also, studies have reported ACF to be beneficial in reducing the delay in TB diagnosis, out of pocket expenditure, unsuccessful treatment outcomes, and incidence of TB [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have reported ACF to be beneficial in increasing case detection [5,6]. Also, studies have reported ACF to be beneficial in reducing the delay in TB diagnosis, out of pocket expenditure, unsuccessful treatment outcomes, and incidence of TB [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Experiences evidenced in the literature, demonstrate successful actions of PC in prevention in relation to illicit drug use, especially in school environments (41) . Thus, PC and its professionals play an important role in the reduction of TB/MD cases, mainly through the implementation of strategies to improve access and diagnosis of these patients through active search (42) and coping with bottlenecks affect the follow-up actions of the cases, such as the absence of a link between professionals and patients and the difficulty of receiving this population in the health units (43) .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, TB cases are reported and passively notified when people with TB present themselves to a health facility. Active case finding (ACF), a proactive TB casefinding approach, has been adopted by countries affected by the epidemic, including Cambodia, to effectively reach people with TB [6][7][8]. Current evidence suggests that TB case-finding interventions at the community level may increase TB case detection [8].…”
Section: Background and Rationalementioning
confidence: 99%
“…Active case finding (ACF), a proactive TB casefinding approach, has been adopted by countries affected by the epidemic, including Cambodia, to effectively reach people with TB [6][7][8]. Current evidence suggests that TB case-finding interventions at the community level may increase TB case detection [8]. In Zimbabwe, Corbett et al demonstrated that ACF using a mobile van approach resulted in a higher yield of smear-positive TB cases compared to ACF conducted via door-to-door visits [9].…”
Section: Background and Rationalementioning
confidence: 99%